A Pre-defined Scheme for Optimum Energy Consumption in Wireless Sensor Network - Halim, N.H.; Isa, A.A.M.; Hamid, A.M.A.; Isa, I.S.M.; Mahyuddin, M.F.M.; Saat, S.; M. Zin, M.S.I. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
One of the fundamental issues that needs a serious attention in Wireless Sensor Network (WSN) is node deployment. A proper node deployment scheme can help extending the lifetime of WSN’s by reducing the energy consumption. In this paper, we implement Improved Harmony Search (IHS) algorithm with several modifications in determining the best position for each sensor node in order to obtain an optimum energy consumption. The number range in selecting the random number to determine a new harmony is expended. Based on the experiment, the result obtained gives lower energy consumption rate. To enhance the energy performance, we test the best sink node’s position to obtain the best position for sink node.